The Discrepancy of ANA and Compartment Bead Patterns Suggestive of a Neuropsychiatry Systemic Lupus Erythematosus (NPSLE) - Munawaroh Fitriah; Lita Diah Rahmawati; Indah Adhita Wulanda; Hani Susianti; Betty Agustina Tambunan (Case Reports in Psychiatry)
Neuropsychiatric systemic lupus erythematosus (NPSLE) exhibits neurological and psychiatric manifestations in systemic lupus erythematosus (SLE) patients, which NPSLE diagnosis can be challenging for rheumatologists. An Indonesian female, 44 years old, complained of two times seizures with 10-min duration, which during seizures were stiff, eyes rolled up, foaming at the mouth, wet the bed, and fainting afterward. The patient also has a history of SLE and received cyclophosphamide therapy 5 years ago. Her clinical condition showed facial and lingual palsy, with central type on the right. Antinuclear antibody indirect immunofluorescence (ANA IF) positive using cytobead ANA with a homogenous pattern and cytoplasmic speckled titer 1/80. Confirmation beads showed positive of dsDNA only. ANA profile showed positive antinucleosome, antihistone, and AMA-M2, and also increased anticardiolipin antibody that supports the diagnosis of NPSLE. The difference in the pattern of ANA IF with confirmation beads suggests the presence of other autoantibodies in NPSLE.